2000
DOI: 10.1143/jjap.39.351
|View full text |Cite
|
Sign up to set email alerts
|

Study of Crystal Growth Mechanism for Poly-Si Film Prepared by Excimer Laser Annealing

Abstract: Recrystallization of polycrystalline silicon (poly-Si) film by excimer laser annealing (ELA) is discussed by considering the experimental results that the three stages of nucleation, textured grain growth and secondary grain growth were observed. Although the phenomenon of nucleation in the amorphous silicon (a-Si) is understood by considering crystallization from the super cooled liquid, the growth mechanisms of the textured grain and secondary grain are not understood by this, because the melt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 6 publications
1
31
0
Order By: Relevance
“…This phenomenon coincides with the result 11) that the ELA process after SPC increased the grain size. From the viewpoint of secondary grain growth, 15) it is observed with ELA, ELA followed by SPC, and SPC followed by ELA. Although partial secondary grain growth occurs for SPC, textured grains are predominantly observed.…”
Section: Methodsmentioning
confidence: 97%
“…This phenomenon coincides with the result 11) that the ELA process after SPC increased the grain size. From the viewpoint of secondary grain growth, 15) it is observed with ELA, ELA followed by SPC, and SPC followed by ELA. Although partial secondary grain growth occurs for SPC, textured grains are predominantly observed.…”
Section: Methodsmentioning
confidence: 97%
“…It is found that, firstly, the tensile stress of the polySi film is released with a progress of secondary grain growth, and secondly, the stress relaxation becomes marked as the hydrogen concentration decreases. Stress Relaxation of Poly-Si Film Formed by Excimer Laser Annealingwhich we previously proposed, 18) in the point that secondary grain growth leads to tensile stress relaxation by the release of strain energy. The origin of the strain energy is thought to be the field of elastic stress around the dislocations at the grain boundary.…”
mentioning
confidence: 95%
“…In our group, the mechanism of secondary grain growth by ELA has been examined to provide a high-quality large-grained film. [15][16][17][18][19][20][21][22][23][24][25][26] Here, the secondary grain is defined as having a grain size larger than the film thickness. It was found by electron spin resonance (ESR) measurement that most of the crystal defects were located at the grain boundary of poly-Si film and that hydrogen in a-Si film influenced the crystallinity of the poly-Si.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such polySi films prepared by the crystallization of amorphous silicon (a-Si) by excimer laser annealing (ELA) have been examined. [1][2][3][4] It is known that hydrogen in a-Si film causes the film exfoliation, and therefore, the H concentration is decreased to below 1 at% by thermal treatment at 500 C for several hours. However, hydrogen desorption does not occur for lowtemperature processes.…”
Section: Introductionmentioning
confidence: 99%